Architectural Elements of the Thracian Cultic Buildings. The Doors (Research Announcements "Heritage BG", 2025)
This article is a part of a wider research ofthe Thracian cultic buildings, concerning the different architectural elements that can be distinguished in their structure. In the sacred architecture, along with their utilitarian function these elements are very often bearers of symbolic meaning. This is why most of them have turned into archetypes of the sacred. The focus ofthis article is the door. Doors take partin the definition ofthe boundary between inside and outside, light and darkness, allowed and forbidden, between the sacred and the profane space, and metaphorically, between the different worlds. They are also the places for crossing this boundary, but according to strict rules, restricting the accessibility. The article examines the prototype of this architectural element as well as its geometry with a regard to the sub-elements that every door consists of. It offers several kinds of classification ofthe doors in the Thracian cultic buildings and specifies different functions and meaning they have in creation of the sacred atmosphere inside. References:Dermendzhiev, N. (2006). Svetlinni kalendarni efekti v arhitekturata na kultovi saorazhenia. In: HELIS V Getite – kultura i traditsiya. Sofia, 155 – 173.Filov, B. (2019). Kupolnite grobnitsi pri Mezek. Sofia.Fol, V. (2007). Skalnite toposi na vyara v Jugoiztochna Evropa i Mala Azia prez drevnostta. (= Studia Thracica, 10). Sofia.Fol, V., Popova, R., & Manova, R. (2021). Tsarskiyat cviat cinobar v trakijskata i rimskata kultura po balgarskite zemi. Sofia.Gergova, D. (2019). Getite, koito obezsmartyavat. Otkritiyata v duhovnata I politicheska stolitsa na getite „Dausdava-Helis”. Sofia.Getov, L. (1988). Maglizhkata grobnitsa. Sofia.Mikov, V. (1954). Antichna grobnitsa pri Kazalak. Sofia.Omir. (1971). Odiseya. prevod ot starogr. Georgi Batakliev. Sofia.Russeva, M. (2000). Trakijska kultova arhitektura v Balgariya. Yambol.Russeva, M. (2006). Trakijskata kultova sgrada kraj Pomorie – shediovar na trakijskata arhitekturna shkola prez rimskata epoha. In: Sbornik materiali ot mezhdunarodnata nauchna konferentsiya BREGAR – MORETO-EVROPA. Modeli na interkulturna komunikatsiya“. Sofia, 22 – 36.Russeva, M. (2013). Metodika na nauchnoto izsledvane na trakijskata arhitektura. Analizi, talkuvane, simvolika. Sofia.Vassileva, D. (2005). Trakijskite grobnitsi. Arhitekturno-metrichno izsledvane. Sofia.Venedikov, I., & Fol, A. (eds.). (1976). Trakijski pametnitsi. Tom 1. Megalitite v Trakiya. Chast 1. Sofia.Vitruvius. (2021). Za arhitekturata. Sofia.Chevalier, J., & Gheerbrant, A. (1996). The Penguin Dictionary of Symbols. London: Penguin Books.Foscari, G. (2014). Elements of Venice. Zürich.Janson, A., & Tigges, F. (2014). Fundamental Concepts of Architecture. The Vocabulary of Spatial Situations. Birkhaeuser, Basel.Kitov, G. (2006). The Valley of the Thracian Kings. In: The Thracian Cosmos: The Sacred Realm of the Kings. Sofia, 40 – 95.Koolhaas, R. (2014). Elements of Architecture. Taschen.Stoev, A., & Stoeva, P. (2006). Rock sanctuary near the village Buzovgrad, Kazanluk Municipality: Megalithic ‘Solar Gate’. In: The Thracian Cosmos: The Sacred Realm of the Kings, Institute of Thracology – Bulgarian Academy of Sciences, 24 – 33.Unwin, S. (1997). Analyzing Architecture. London.
Keywords: Thracian cultic buildings; architectural elements; doors